Cdse And Tio2 Photoanode By Electrophoretic Deposition For Quantum Dot Sensitized Solar Cell - Hay, Mar Aung Kyaw (2020)
CdSe nanoparticles was used as a photon sensitizer in quantum dot sensitized solar cell (QDSSC). Mesoporous structure is desired for TiO2 wide band gap semiconductors to provide large surface area for absorption of more QDs in harvesting visible light efficiency. Common method to make QDSSC is to complete the CdSe with TiO2 for charge transfer. But, the problem with this system is that photoexcited electron need to travel a long pathway (the thickness of TiO2) before its reach to the conductive substrate, where the photoexcited electron is susceptible to recombination with the sub-band gap state of TiO2. Mixed CdSe-TiO2 photoanodes will create efficient electron injection from CdSe conduction band to the TiO2 electrode effectively in order to reduce the recombination and improve the efficiency. In this research, CdSe nanoparticles were synthesized by hot injection method and using different amount of TOPO ligand. CdSe nanoparticles were dispersed in chloroform after purification process. 8 g TOPO amount of CdSe were used for deposition process. CdSe was deposited on fluorine doped tin oxide (FTO) substrate by using electrophoretic deposition method (EPD) with various EPD parameter. CdSe was deposited on TiO2 film and mixing CdSe-TiO2 were deposited on FTO substrate. TiO2 nanoparticles were successfully prepared by modification using both propionic acid and n-hexylamine and TiO2 nanoparticles dissolved in chloroform. TiO2 was deposited on fluorine doped tin oxide (FTO) substrate by using electrophoretic deposition method (EPD) with various EPD parameter. For CdSe/TiO2 film, TiO2 was deposited on FTO first then this film was heated 450 °C for 3 hours. Then, CdSe was deposited on heated TiO2 film. For mixed CdSe-TiO2 films, CdSe and TiO2 was mixed together and deposited on FTO substrate. CdSe/TiO2 film and mixed CdSe-TiO2 film were prepared by EPD method as photoanode. For QDSSC, CdSe/TiO2 film and mixed CdSe-TiO2 film was used as photoanode, copper (II) sulfide (Cu2S) as counter electrode and was used polysulfide electrolyte. These photoanode, counter electrode and electrolyte were assembled for I-V and EIS measurements. The highest efficiency of CdSe/TiO2 film was 2.1% and 0.04% for the mixed CdSe-TiO2 films. From the result of EIS measurement, the Rct value of CdSe/TiO2 films and mixed CdSe-TiO2 films were 51 Ω and 75 Ω. Thus, the CdSe/TiO2 films produced higher efficiency than mixed CdSe-TiO2 films in QDSSC application.